AL-ISMUL-MUQTARINU BI-AL DALAM NOVEL MĀ WARĀ AN-NAHR KARYA TĀHĀ HUSAIN ANALISIS FUNGSI - Dewi Ferawati (Cross-border, 2018)
This research was conducted to find out what al is used by Tahā Husain in the novel Mā Warā' an-Nahr and the function of ism that begins after being arranged in a sentence. The question in this study is how the levels of al-nucleus after the melting occurred. This research is a structural research and uses the agih method. The technique used is the basic technique, namely the i'rāb technique, and the advanced technique is the lesap technique. This study concludes that al contained in the novel Mā Warā' an-Nahr is al-ashliyyah, while al-maushūlah is not found in the novel. From the i'rāb technique, it is found that the position of the ism that exists in Mā Warā' an-Nahr's novel functions as musyāru ilaih, maf'ūl bih, fā'il, zarf, mudāf ilaih, and ism inna. becomes ungrammatical and cannot be interpreted, because al has a high level of core so that its existence absolutely must be in the sentence. However, there are also sentences that still remain grammatical after the al is removed, but the position of the ism that is discarded has changed and the meaning has also changed, so that it is not in accordance with the author's intended purpose.